Transcultural Adaptation and Validation of the Spanish Version of the Visual Analogue Scale for the Foot and Ankle (VASFA) - Cervera-Garvi, Pablo; Galán-Hurtado, María Hermas; Marchena-Rodríguez, Ana José; Chicharro-Luna, Esther; Guerra-Marmolejo, Cristina; Díaz-Miguel, Salvador Francisco; Ortega-Ávila, Ana Belén (MDPI, 2023)
Background: The main aim of this study is to perform a cross-cultural adaptation and validation of the Visual Analogue Scale for the Foot and Ankle (VASFA) questionnaire, creating a Spanish-language version (VASFA-Sp), and to determine the measurement properties of this instrument. Methods: VASFA was cross-culturally translated into Spanish following the guidelines of the International Society for Pharmacoeconomics and Outcomes Research (ISPOR). The study sample was composed of 228 participants who were recruited from February to May 2022. All were at least 18 years old, gave signed informed consent to take part and properly completed the Foot and Ankle Ability Measures-Sp and VASFA-Sp questionnaires. Cronbach's alpha and test/re-test reliability values were calculated. Structural validity was assessed via exploratory factor analysis. Results: The 228 patients included in the final analysis presented the following characteristics: 35.53% were male and 64.47% were female; the mean age was 35.95 (18-81) years; and the mean body mass index was 23.79. Internal consistency was excellent. The Cronbach's alpha for VASFA-Sp was 0.96 and the intraclass correlation coefficient was 0.932 (95% CI; 0.84 to 0.97). Exploratory factor analysis identified one main factor. Conclusions: VASFA-Sp is a reliable, valid and sensitive questionnaire that is suitable for measuring perceived foot and ankle function impairment in a Spanish-speaking population.
Keywords: Pies - Lesiones y heridas - Test; Cross-cultural adaptation; Reliability; Scale; Validity; Function; Pain